OTA 2.0: An Advanced and Secure Blockchain Steganography Algorithm - TAKAOĞLU, Mustafa; ÖZYAVAŞ, Adem; AJLOUNİ, Naim and DURSUN, Taner and TAKAOĞLU, Faruk and DEMİR, Selin (International Journal of Computational and Experimental Science and Engineering, 2023)
Blockchain technology, a disruptive force beyond Bitcoin, is finding applications across various fields, including scientific disciplines like steganography – the art of data hiding. Digital steganography has gained momentum with data digitization, especially in multimedia environments like images, text, audio, and videos. Blockchain’s integration into steganography has led to interesting developments, like the OTA (OzyavasTakaoglu-Ajlouni) algorithm introduced in 2021. The OTA algorithm consists of two stages: the OTA-steganography algorithm and the OTA-chain algorithm (private blockchain). Developed using Java and JavaScript, the OTA platform utilises OTA-coins as its native currency. Previous versions allowed various file types as cover-multimedia, with the secret message encrypted using the Vernam Cipher symmetric encryption and hidden using OTA steganography. Unlike other steganography methods, OTA doesn’t alter the cover-multimedia but uses bit-level data marking. In the OTA system, the marked data indices are stored in 1 KB arrays and transmitted to the receiver as transactions via OTA-chain, each incurring a fixed fee of 1 OTA-coin to prevent DDoS attacks. The OTA 2.0 algorithm improved on the previous version by switching to Hyperledger Fabric protocol, which offers open-source, permissioned blockchain solutions, decentralisation capabilities, and self-sovereign identity support. The new version also enhanced block creation time to 2 seconds, increased block size to 90 MB, and employed a 4-bit marking pattern while eliminating transaction fees. Thanks to its innovative key-sharing method and permissioned architecture, OTA 2.0 proves resistant to steganalysis methods commonly used in steganography studies.